New insights into the oxidation mechanisms of a Ferritic-Martensitic steel in high-temperature steam. (1st August 2020) - Shen, Zhao; Chen, Kai; Yu, Hongbing; Jenkins, Benjamin; Ren, Yanru; Saravanan, Naganand; He, Guanze; Luo, Xiaonan; Bagot, Paul A.J.; Moody, Michael P.; Zhang, Lefu; Lozano-Perez, Sergio
Abstract: The microstructure of the surface oxide film formed on an Fe-9Cr Ferritic-Martensitic (F-M) steel after exposure to deaerated high-temperature steam at 600°C for 100 h has been analyzed in detail by advanced characterization techniques. The surface oxide film has been revealed to have a triplex structure, including an outer oxide layer, an inner oxide layer, and an internal oxide layer. Although the outer and inner oxide layers are continuous, the internal oxide layer has been proved to consist of interconnected metallic and chromite phases, which is a typical feature of internal oxidation. The formation mechanisms of each layer have been discussed, finding that, contrary to what the available space model suggests, an external oxidation is not the controlling oxidation mechanism of F-M steels in high-temperature steam. The higher resolution used in this study confirms that the controlling mechanism is internal oxidation. Graphical abstract: Image, graphical abstract